MRI Guided Focused Ultrasound Thalamotomy for Moderate-to-Severe Tremor in Parkinson’s Disease - Ilana Schlesinger; Ayelet Eran; Alon Sinai; Ilana Erikh; Maria Nassar; Dorith Goldsher; Menashe Zaaroor (Parkinson's Disease)
Background. Thalamotomy is effective in alleviating tremor in Parkinson’s disease (PD). Methods. Seven PD patients, mean age 59.4 ± 9.8 years (range, 46–74) with a mean disease duration of 5.4 ± 2.8 years (range, 2–10) suffering from severe refractory tremor, underwent ventral intermediate nucleus thalamotomy using MRI guided focused ultrasound (MRgFUS), an innovative technology that enables noninvasive surgery. Results. Tremor stopped in the contralateral upper extremity in all patients immediately following treatment. Total UPDRS decreased from 37.4 ± 12.2 to 18.8 ± 11.1 (p=0.007) and PDQ-39 decreased from 42.3 ± 16.4 to 21.6 ± 10.8 (p=0.008) following MRgFUS. These effects were sustained (mean follow-up 7.3 months). Adverse events during MRgFUS included headache (n=3), dizziness (n=2), vertigo (n=4), and lip paresthesia (n=1) and following MRgFUS were hypogeusia (n=1), unsteady feeling when walking (n=1, resolved), and disturbance when walking tandem (n=1, resolved). Conclusions. Thalamotomy using MRgFUS is safe and effective in PD patients. Large randomized studies are needed to assess prolonged efficacy and safety.